A study on market interdependence of futures markets with its underlying assets: analysis on Asian emerging market (Hong Kong, Malaysia, Korea) / Noor Atika Buang - Buang, Noor Atika (Faculty of Business and Management, 2011)
This paper attempts to investigate the markets interdependence between the spot and futures markets in Asian emerging markets. The weekly data of closing price of stock index and settlement price of stock index futures in emerging country namely Hong Kong, Malaysia and Korea was collected as variables in this study. The data was collected for 5 years period started from 1st January 2005 until 31st December 2010. The model used in this study was Single Linear Regression as the estimator in this study. The study reveals that there are effects on relationship between the spot price and futures prices. The result indicates that there is a significant positive between the spot and futures price. Furthermore, the result reveals that emerging countries has a bidirectional relationship between that spot and futures markets. It means the spot and futures price are move proportionally together. The analysis on the correlation of futures markets return shows that futures markets are highly correlated with the spot markets. Overall there is a bidirectional relationship in spot and futures markets in Hong Kong, Malaysia and Korea and futures markets are highly correlated with spot markets. The result from this study can be used for predicting the price of spot markets and futures markets by the market participants especially investor and markets analyst.